口腔症状よりムコール症を発見しえた急性骨髄性白血病患者の1例 - 滝沢, 茂太; 鈴木, 晶子; 内藤, 慶子; 蓜島, 桂子; 野町, 晃彦; 内藤, 克美 (日本口腔外科学会雑誌, 2015)
As perioperative oral functional management has been covered by national health insurance since fiscal 2012 in Japan, these services have been provided in the Department of Oral and Maxillofacial Surgery, Hamamatsu Medical Center. We report a case of mucormycosis developing in the oral cavity during the perioperative oral functional management of a patient with acute myeloid leukemia who underwent bone marrow transplantation. Rhinocerebral mycosis usually arises in the nasal cavity, paranasal sinuses, or oculus. In our patient, discoloration of the maxillary gingiva was the first symptom, and only oral findings were useful for diagnosis. Patients receiving perioperative oral functional management are compromised and at risk for rare infectious diseases. In conclusion, we recognize that it is very important to manage oral function in perioperative patients not only for the maintenance of oral function, but also for the early detection of oral abnormalities.